Black Carbon Concentration and Potential Source Regions: A Case Study of the Yellow River Basin in Shandong Province, China - Yuxia Wang; Yanni Rong; Kai Qu; Qing Zhao; Yingming Jiang; Xiaolei Bao; Yang Wang (Aerosol and Air Quality Research)
Abstract Black carbon (BC) concentrations and potential source regions were analyzed for nine cities in the Yellow River Basin in Shandong Province from September 2021 to August 2022. Higher BC concentrations were found in Jinan, Tai’an, Jining, and Dezhou, situated in the central part of the study area. BC concentration exhibited the highest values in winter, followed by autumn, spring and summer in all cities excluding Jinan. The monthly average BC concentrations in Jinan ranged from 0.69 to 3.92 µg m–3. BC concentration exhibited a pronounced diurnal variation, which decreased from the morning peak to afternoon. The analysis of related pollutants revealed that BC in Jinan shared similar sources with PM2.5 and CO, which were influenced by the distribution of the surrounding high-energy-consuming industries. BC exhibits a correlation of 0.51 and 0.56 with SO2 and NO2 in summer, indicating BC is more affected by traffic emissions compared with industrial sources in summer in Jinan. High BC concentration in summer in Jinan is associated with poor diffusion conditions due to terrain and meteorology. High BC concentrations may contribute high land surface temperature (LST) in Jinan during summer. The backward trajectory and potential source regions analysis showed that the potential source area of BC varied considerably in different seasons. In winter and autumn, BC mainly came from local emissions. While in spring and summer, regional transport had equal contribution to BC as local emissions, which cannot be ignored. The findings provide insights for protecting the regional atmospheric environment and promoting high-quality development of the study area.